Principles and labs for physical fitness - Hoeger, Werner W. K.; Hoeger, Sharon A. (Wadsworth, Cengage Learning, 2012)
Takes a personalized approach that guides you through the development of an attainable fitness program. This title focuses on fitness topics, including body composition, cardiorespiratory endurance, muscular strength and flexibility